Life's a dream - Calderón de la Barca, Pedro, 1600-1681 (University Press of Colorado, 2004)
"Life's a Dream (La vida es sueno, 1636) is the best known and most widely admired play of Catholic Europe's greatest dramatist, Pedro Calderon de la Barca. Calderon's long life (1600-1681) witnessed both the pinnacle and collapse of Spanish political power as well as the great flowering of Spanish classical literature."